Comparison of oral hygiene status before and after health education among 12-18-year-old patients - S G Ramesh Kumar; M B Aswath Narayanan; D Jayanthi (Wolters Kluwer Medknow Publications, 2016)
Introduction: Adolescence is a crucial period of transition with personal responsibility for preventing dental disease. The outcome of health education program has shown considerable results. The knowledge which children received during health education program paves way for the first steps to their healthier life. Aim: To study the impact of oral health education on oral hygiene status of patients aged 12-18 years, attending outpatient department. Materials and Methods: A hospital-based randomized controlled clinical trial with 100 participants (allocated into 50 study group and 50 control group) aged 12-18 years attending the outpatient department, constituted this study. Participants were assessed for basic oral health knowledge, attitude, and practices using a questionnaire. The oral hygiene status was assessed using oral hygiene index (OHI) and patient hygiene performance (PHP) index. After oral prophylaxis, oral health education was given only to study group. Both groups were reassessed after 4 weeks. The values were compared. Statistical analysis was done using SPSS version 15. Results: Comparison shows more reduction of mean OHI score, and PHP score in the study group than control group with a significant P value. Conclusion: Oral health education demonstrates the satisfactory impact on oral hygiene among adolescents.